2017
DOI: 10.2320/matertrans.l-m2017823
|View full text |Cite
|
Sign up to set email alerts
|

Prediction and Experimental Validation of Cooling Rate Dependence of Viscoplastic Properties in a Partially Solidified State of Al–5 mass%Mg Alloy

Abstract: To predict hot tearing in direct chill (DC) casting and shape casting of aluminum alloys using thermal stress analysis, cooling rate dependence of viscoplastic properties in a partially solidi ed state is indispensable. Based on viscoplastic properties determined from experiments, this study develops a method to predict the temperature dependence of viscoplastic properties at an arbitrary cooling rate through the Clyne-Kurz microsegregation model. For validation of the developed method, tensile tests were perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 29 publications
2
5
0
Order By: Relevance
“…The average expansion coefficient was determined from the following experimentally obtained results in an earlier work. During solidification, an Al4%Mg alloy contracts by around 0.2% during solidification 32) in the temperature range between 570°C, which is consistent with the ZST, 14,26,27) and the solidus (448°C). Figure 3(b) presents the thermal strain at each temperature range which reproduces the contraction behavior described above.…”
Section: Constitutive Models For the Alloy Ac7asupporting
confidence: 74%
See 4 more Smart Citations
“…The average expansion coefficient was determined from the following experimentally obtained results in an earlier work. During solidification, an Al4%Mg alloy contracts by around 0.2% during solidification 32) in the temperature range between 570°C, which is consistent with the ZST, 14,26,27) and the solidus (448°C). Figure 3(b) presents the thermal strain at each temperature range which reproduces the contraction behavior described above.…”
Section: Constitutive Models For the Alloy Ac7asupporting
confidence: 74%
“…14,26,27) Under the cooling conditions used for this study, it was confirmed that the ZST of the alloy has almost no cooling rate dependence. 14) The temperature at the occurrence of hot tearing T HT was determined from the experimentally obtained thermal load described in section 2.1, i.e. the temperature at which the first derivative of the loadtime curve is the maximum.…”
Section: Stress Analysissupporting
confidence: 62%
See 3 more Smart Citations